How Charles Kelman Invented phacoemulsification in the 1960s: A reappraisal - Christopher T. Leffler; Stephen G. Schwartz (Heliyon)
Purpose: To determine the timing of the development of phacoemulsification by Charles Kelman, which occurred when he modified an ultrasonic dental tool (Cavitron, NY) to emulsify cataracts so that they could be removed through small incisions. Design: Review of primary source materials and scholarly literature, and interviews. Methods: We reviewed the John A. Hartford Foundation files related to Kelman, and the lecture notes of Cavitron engineer Anton Banko. We interviewed his first wife, two people who worked in his lab (an assistant, and Ronald Odrich, a periodontist), Kelman's former fellow (Norman Medow), Banko's son, and the son of the Kelman family dentist, Lawrence Kuhn. Results: Kelman initially pursued other ideas for cataract surgery, including cryoextraction, starting in the fall of 1962. His first grant, which covered small-incision cataract surgery, became active in January 1964. Kelman could have learned of the Cavitron ultrasonic dental prophylactic instrument from a number of sources, including from his first wife, who worked in Kuhn's dental office and recalled mentioning the device to Kelman as early as 1962. In addition, periodontist Odrich first appears in the Foundation files as a visiting dentist in the Kelman laboratory at about the same time that Kelman began working with the Cavitron corporation in early 1965. According to both Kelman and Kuhn: 1) Kelman first saw the Cavitron at Kuhn's office, and 2) Kelman and Kuhn first tested the Cavitron on a previously-extracted cataract at Kuhn's office. In Kuhn's recollection, the device failed to emulsify the lens. In February 1965, when Kelman's grant had 2 years remaining, Kelman began working with the Cavitron corporation to modify the instrument for cataract surgery. The first time the Cavitron instrument was able to remove a cataract in any species in a manner deemed a success was in a cat's eye on March 23, 1966. The first two phacoemulsifications in human patients took place between April and June of 1967, although the exact dates are unknown. Conclusions: Kelman could have learned about the Cavitron ultrasonic instrument from his first wife, from Odrich (a periodontist who worked in the Kelman lab), and from Kuhn, the Kelman family dentist. By all accounts, Kelman and Kuhn, his dentist, collaborated on several important steps in early phacoemulsification development. Kelman probably became aware of the Cavitron ultrasonic instrument earlier than is generally recognized, but multiple modifications of this device were required to permit its use for cataract surgery.